High-pressure experimental data of CO 2 + mitotane and CO 2 + ethanol + mitotane mixtures - Giufrida, W. M. (2011)
This work presents new experimental phase equilibrium data for mitotane in supercritical CO 2 and mitone in supercritical CO 2 plus ethanol. The synthetic-static method in a high-pressure variable-volume view cell was used to measure the solid-fluid (SF) and the fluid-fluid (FF) equilibrium data. The phase equilibrium experiments were carried out in the temperature range from (298 to 333) K and in the pressure range from (3.44 to 21.84) MPa. The Peng-Robinson equation of state (PR-EoS) was used for describing the fluid phases, and an expression for the fugacity of pure solid mitotane was used for representing the solid phase. This made it possible to model the SF and FF equilibrium data for the CO 2 + mitotane mixtures. Fair agreement was found between experimental and calculated values.